Narrativas en Torno a las Competencias Emocionales de Mujeres Denunciantes de Violencia Conyugal que Asisten al Centro De Atención Psicológico de la Universidad Antonio Nariño - Álzate García, Lina Marcela (Universidad Antonio Nariño, 2024)
The present research sought to describe the narratives of women complaining about conjugal violence, identifying the before, during and after the cycle of violence around emotional competencies. Using a qualitative approach, a description of the participants’ reports was obtained using semi-structured interviews, which allowed an acceptable flexibility and at the same time uniformity in the results, thus, making it possible to carry out the respective analysis of the narratives, responding to the categories proposed. The analysis allowed to identify and describe the perception of risk, the modes of reaction to the aggression, the resources to leave the violent cycle and the participants' current life experience.